2019
DOI: 10.1021/acs.jpcc.8b10261
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Eu2+ Dopant in CsPbBr3 Perovskites: A First-Principles Study

Abstract: We study the stability of the rare-earth dopant, Eu, in metal-halide perovskite CsPbBr3 with cubic and orthorhombic structures from first-principles calculations. In these perovskites, Eu is substitutionally doped on Pb sites because of their comparable ionic sizes which lead to only a small strain in the doped system. Accordingly, our results show that the cost of Eu doping is quite small compared to the values in other common hosts such as GaN. This makes these perovskites excellent candidates to develop rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 35 publications
(60 reference statements)
3
36
1
1
Order By: Relevance
“…More recently, By partially substitute Pb 2+ with Eu 3+ , a stable α‐phase CsPbI 2 Br perovskite was obtained at room temperature, showing a maximum PCE of 13.71% . All of these findings demonstrated that smaller Eu 3+ can be doped into the inorganic perovskites to improve their photovoltaic performance and stability …”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…More recently, By partially substitute Pb 2+ with Eu 3+ , a stable α‐phase CsPbI 2 Br perovskite was obtained at room temperature, showing a maximum PCE of 13.71% . All of these findings demonstrated that smaller Eu 3+ can be doped into the inorganic perovskites to improve their photovoltaic performance and stability …”
Section: Introductionmentioning
confidence: 90%
“…For this purpose, a series of doping strategies have been carried out by incorporating some smaller metal cations into the perovskite lattice to modulate photoelectronic properties and improve the phase stabilities of inorganic perovskite materials. For instance, some works proposed to partially substitute B‐site cations (Pb 2+ , 120 pm) with smaller lanthanide ions such as Ce 3+ (103 pm), Eu 3+ (95 pm), Sm 3+ (111 pm), Er 3+ (88 pm), and so on in the inorganic perovskites . It demonstrated that the addition of lanthanide ions can effectively improve the photovoltaic performance and stability of inorganic PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 The photovoltaic properties and the electronic structures of the lanthanide and actinide perovskite compounds were characterized by experimental results using first-principles calculation. [37][38][39] Rare-earth-based compounds have unique types of physical phenomena owing to their heavy-electron behaviours, such as their magnetic properties, fluorescence characteristics, superconductivity and photovoltaic application. [40][41][42][43] For example, the 4f orbitals of europium are blocked by the closed shell structure of 5s-5p 6 , making them less susceptible to crystal fields in the coordination structure.…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanide ions have been widely investigated as the optically active dopants in CsPbX 3 inorganic perovskite nanocrystals, achieving high photoluminescence quantum yield (PLQY), multiple color emission, and quantum cutting effect for lighting and labeling applications. [114][115][116][117] Inspired by those exciting developments, most of the lanthanide ions, such as La 3þ , Ce 3þ , Sm 3þ , Eu 3þ , Tb 3þ , Ho 3þ , Er 3þ , and Yb 3þ , have been considered as the promising B-site dopants to improve the optoelectronic properties and the stability of inorganic CsPbX 3 perovskite crystal for solar cell application in the past 2 years. [118][119][120][121][122][123][124][125] Jena et al reported that the B-site doping of Eu could greatly enhance the stability of CsPbI 3 perovskite in ambient condition and reduce the nonradiative recombination within CsPbI 3 perovskite films.…”
Section: Trivalent Cations Dopingmentioning
confidence: 99%